(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
This study was done to investigate the prevalence of umbilical hernia of calves and its risk factors during the period from July, 2012 to January, 2013 at Tangail Sadar Upazila of Bangladesh. A total number of 1053 animals were examined during the study period where diagnosis based on the clinical history, clinical signs, palpation, needle puncture, auscultation. Then the animals was subdivided into some risk factors such as age, sex, breed, history of umbilical infection which may be lead to umbilical hernia. It was observed that male (61.10%) were in more risk than that of female (38.90%). In case of male calves maximum occurrence of the disease were in the age group of 1-3 months (45.45%) followed by <01 month of age group (36.36%) and least occur in 3-6 months of age group (18.18%) and in case of female calves maximum occur in the age of 1-3 months (71.43%) followed by in the age group of <01 month and 3-6 months (14.29%). The occurrence of umbilical hernia was more common in crossbreed calves (77.78%) than that of indigenous calves (22.22%). In case of crossbreed animals, male calves (44.44%) were more susceptible than in female calves (33.33%). In case of indigenous animals, male and female calves (11.11%) are more or less equally susceptible to the disease. In this study other umbilical infection likes umbilical abscess and navel ill which enhance the probability of occurrence of umbilical hernia, although it may be inherited in a dominant or recessive mode. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (2), 154-158